Root phenotypic diversity in common bean reveals contrasting strategies for soil resource acquisition among gene pools and races - Jochua, Celestina N.; Strock, Christopher F.; Lynch, Jonathan P. (Crop science, 2020)
Although genetic diversity for aboveground traits has been well characterized in common bean (Phaseolus vulgaris L.), little is known about population‐specific variation within this species for root architecture. To assess the diversity of root phenotypes, a total of 196 accessions from a core collection were evaluated in the laboratory and field in Pennsylvania, USA, and Chokwe, Mozambique. Substantial phenotypic variation for 15 root phenes exists among gene pools, races, and genotypes. Principal component analysis revealed that Andean and Mesoamerican gene pools and races have distinct integrated root phenotypes. Unsupervised cluster analyses of root phenes identified five groups with distinct integrated root phenotypes and soil foraging strategies. Although integrated phenotypes associated with adaptation to drought and low P availability were found in both gene pools, phenotypes for drought adaptation were more prevalent among Mesoamerican accessions, whereas phenotypes for adaptation to suboptimal P were more common among Andean accessions. These genotypic differences in root phenotypes reflect contrasting strategies for soil resource acquisition and may possibly have evolved as an adaptation to the edaphic conditions in the environments to which Andean and Mesoamerican gene pools are endemic. This diversity of root architectural strategies for soil exploration can serve as an important resource for breeding programs and hybridization between gene pools may result in the generation of novel root phenotypes with improved soil resource acquisition.